Adaptive management of natural resources—framework and issues - Williams, Byron K. (Journal of Environmental Management, 2011)
Adaptive management, an approach for simultaneously managing and learning about natural resources, has been around for several decades. Interest in adaptive decision making has grown steadily over that time, and by now many in natural resources conservation claim that adaptive management is the approach they use in meeting their resource management responsibilities. Yet there remains considerable ambiguity about what adaptive management actually is, and how it is to be implemented by practitioners. The objective of this paper is to present a framework and conditions for adaptive decision making, and discuss some important challenges in its application. Adaptive management is described as a two-phase process of deliberative and iterative phases, which are implemented sequentially over the timeframe of an application. Key elements, processes, and issues in adaptive decision making are highlighted in terms of this framework. Special emphasis is given to the question of geographic scale, the difﬁculties presented by non-stationarity, and organizational challenges in implementing adaptive management.

Improving our legacy: Incorporation of adaptive management into state wildlife action plans - Fontaine, Joseph J. (Journal of Environmental Management, 2011)
The loss of biodiversity is a mounting concern, but despite numerous attempts there are few large scale conservation efforts that have proven successful in reversing current declines. Given the challenge of biodiversity conservation, there is a need to develop strategic conservation plans that address species declines even with the inherent uncertainty in managing multiple species in complex environments. In 2002, the State Wildlife Grant program was initiated to fulﬁll this need, and while not explicitly outlined by Congress follows the fundamental premise of adaptive management, ‘Learning by doing’. When action is necessary, but basic biological information and an understanding of appropriate management strategies are lacking, adaptive management enables managers to be proactive in spite of uncertainty. However, regardless of the strengths of adaptive management, the development of an effective adaptive management framework is challenging. In a review of 53 State Wildlife Action Plans, I found a keen awareness by planners that adaptive management was an effective method for addressing biodiversity conservation, but the development and incorporation of explicit adaptive management approaches within each plan remained elusive. Only w25% of the plans included a framework for how adaptive management would be implemented at the project level within their state. There was, however, considerable support across plans for further development and implementation of adaptive management. By furthering the incorporation of adaptive management principles in conservation plans and explicitly outlining the decision making process, states will be poised to meet the pending challenges to biodiversity conservation.

An Introduction to Adaptive Management for Threatened and Endangered Species - Runge, Michael C. (Journal of Fish and Wildlife Management, 2011)
Management of threatened and endangered species would seem to be a perfect context for adaptive management. Many of the decisions are recurrent and plagued by uncertainty, exactly the conditions that warrant an adaptive approach. But although the potential of adaptive management in these settings has been extolled, there are limited applications in practice. The impediments to practical implementation are manifold and include semantic confusion, institutional inertia, misperceptions about the suitability and utility, and a lack of guiding examples. In this special section of the Journal of Fish and Wildlife Management, we hope to reinvigorate the appropriate application of adaptive management for threatened and endangered species by framing such management in a decision-analytical context, clarifying misperceptions, classifying the types of decisions that might be amenable to an adaptive approach, and providing three fully developed case studies. In this overview paper, I define terms, review the past application of adaptive management, challenge perceived hurdles, and set the stage for the case studies which follow.

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (White Paper #1104, 2011)